Correction: Caspase-1-Like Regulation of the proPO-System and Role of ppA and Caspase-1-Like Cleaved Peptides from proPO in Innate Immunity. - Miti Jearaphunt; Chadanat Noonin; Pikul Jiravanichpaisal; Seiko Nakamura; Anchalee Tassanakajon; Irene Söderhäll; Kenneth Söderhäll (PLoS Pathogens)
[This corrects the article DOI: 10.1371/journal.ppat.1004059.].